Strengthening the Education Sector Response to School Health, Nutrition and HIV/AIDS in the Caribbean Region : A Rapid Survey of 13 Countries - O'Connell, Tara; Venkatesh, Mohini; Bundy, Donald (World Bank, Washington, DC, 2013)
Recent studies point to a number of current and emerging concerns in the health and nutrition of school-age children in the Caribbean region. Critical among them are: infectious diseases including HIV and other sexually transmitted infections (STIs); non-communicable diseases (NCDs); and violence. Common health conditions including diabetes, hypertension and heart disease in the adult population can be positively linked to unhealthy lifestyles in youth. These health challenges, combined with a large school-age population, which in some countries may be a sizable third of the overall population, make a strong national response to the health and nutritional needs of school-age children particularly vital. As lifelong patterns of behavior and thinking are established during youth, it is critical to ensure early and widespread promotion of healthy practices related to sexual behavior, nutrition and a healthy lifestyle in general in the school-age population, resulting in a healthier adult population in the future. The rapid survey and this resulting report contribute to the collection of locally relevant evidence, as well as regional information relevant to School Health and Nutrition (SHN) and HIV, to build a sound evidence base at both country and regional levels to inform policy and strategy. It has further application as a resource for knowledge sharing as it provides a comparative perspective on activities and initiatives thus far implemented throughout the Caribbean region, and on the allocation and mobilization of resources used to support these activities and initiatives.